Analisis pengaruh suku bunga, inflasi, debt to equity ratio (DER), ukuran perusahaan, dan umur perusahaan terhadap profitabilitas perusahaan sub sektor telekomunikasi yang terdaftar di BEI tahun 2016-2020 - Irni Yunita; Naurah Salsabila Ramadhana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Currently, investment activities are very popular with the people of Indonesia and become one of the aspects that affect the economic development of a region. The telecommunications sector is one of the sectors whose stocks show positive movements. One of the ways to determine the capability of a company is to look at the level of profitability of the company. Profitability can be influenced by factors originating from outside the company such as interest rates, inflation, and exchange rates which are generally used as benchmarks for the economy. Meanwhile, there are also factors that come from within the company itself and are usually related to decision making and strategies to be carried out such as leverage, DER, company size, and company age. The purpose of this study was to determine the effect of Interest Rates, Inflation, DER, Company Size, and Company Age on Profitability, with the object being the telecommunication sub-sector companies listed on the IDX in 2016-2020. This research is included in quantitative research with the method used is multiple linear regression, using F-test and t-test for hypothesis testing. The results of this study prove that interest rates, inflation, DER, company size, and company age simultaneously have a significant effect on company profitability. Partially, DER, firm size, and firm age have a significant effect, however, interest rates and inflation have no significant effect on profitability.